Reliability and minimal detectable change of the mini-BESTest in adults with spinal cord injury in a rehabilitation setting. (2nd January 2021) - Roy, Audrey; Higgins, Johanne; Nadeau, Sylvie
ABSTRACT: Background : The mini-Balance Evaluation Systems Test (mini-BESTest) is a valid tool for assessing standing balance in people with spinal cord injury (SCI). Its reliability has not yet been investigated with this population. Objective : To assess the test-retest and inter-rater reliability of the mini-BESTest in adults with SCI in a rehabilitation setting. Methods : Twenty-three participants admitted in a rehabilitation center following an SCI (mean age = 52.2 years, SD = 14.5; 13/23 tetraplegia; 14/23 traumatic injury) and able to stand 30 seconds without help were recruited. They were evaluated twice with the mini-BESTest to establish the test-retest reliability (interval of 1 to 2 days). One of the two sessions was video-recorded to establish the inter-rater reliability (3 physiotherapists). Intraclass correlation coefficients (ICC2, 1 ), weighted kappa (Kw ) and Kendall's W were used to determine reliability of total score and individual items. Minimal detectable changes (MDC) were computed. Results . The mini-BESTest total scores showed excellent test-retest (ICC = 0.94) and inter-rater (ICC = 0.96) reliability. Reliability of 50% of the individual items was acceptable to excellent (Κw and W = 0.35–1.00). The MDC of the mini-BESTest total score was 4 points. Conclusion : The mini-BESTest is a reliable tool to assess standing balance in adults with an SCI. A minimal change of 4 points on the total scale is needed to be confident that the change is not a measurement error between two sessions or two raters.